The evolution of financial market infrastructure: From digitalization to tokenization - Dong Guo; Peng Zhou (Cardiff University, Cardiff Business School, 2023)
This paper examines the historical development and cross-sectional heterogeneities of Financial Market Infrastructure (FMI). From an evolutionary perspective, we review and compare FMIs in the US, Europe, and China. We identify an emerging trend in which the development of FMI is transitioning from digitalization to tokenization with the rise of Distributed Ledger Technology (DLT). Digitalization reinforces centralization, while tokenization promotes decentralization, posing complex challenges to regulatory framework which is also part of FMI. We then specifically analyze DLT-based FMI in the bond market, evaluate different models of tokenization, and propose a heterogeneous consortium blockchain solution.
Keywords: 330; digitalization; tokenization; blockchain; bond